ANGKA KEMATIAN PASIEN AIDS DENGAN INFEKSI OPORTUNISTIK OTAK DI RSCM - Arthur H.P. Mawuntu*, Darma Imran**, Jofizal Jannis**, Joedo Prihartono*** (NEURONA, 2011)
INTRODUCTION BRAIN OPPORTUNISTIC INFECTIONS IS THE MOST FREQUENT AIDS COMPLICATION IN NEUROLOGY WARD IN RSCM HOWEVER THE PREVALENCE MORTALITY AND CHARACTERISTIC OF THE PATIENTS IN THE LAST THREE YEARS WERE UNKNOWN